The usefulness of bacteriological screening in wound healing aspect after vulvectomy - Olejek, Anita; Kozak-Darmas, Iwona; Kellas-Sleczka, Sylwia; Nowak, Leszek (Menopause Review/Przegląd Menopauzalny, 2005)
The aim of this study was wound healing in 43 women after vulvectomy because of vulvar squamosus cell carcinoma after surgery procedures in years 2003-2004, in departament of obstetrics and gynecology in Bytom. In 90.7% patients we observed pathological bacterial flora in swabs from vulva. We observed Escherichia coli , Streptococcus β haemoliticus gr. B, Escherichia coli haemoliticum , Staphylococcus aureus , Proteus mirabilis , Gardnerella vaginalis , Morganella morgani oraz Pseudomonas aeruginosa . Before operation all women with pathological bacterial flora were treated with antibiotics. In 62.8% women after surgery procedures we observed well wound healing and in 37.2% patients the process of wound healing was disturbed. In that group we observed Escherichia coli , Staphylococcus aureus , Proteus mirabilis , Streptococcus β haemoliticus gr. B, Morganella morgani oraz Pseudomonas aeruginosa .